Low-dose statins restore innate immune response in breast cancer cells via suppression of mutant p53 - Wang, Zi; Shi, Meina; Liu, Beijia; Zhang, Xuening; Lin, Wanjun; Yang, Yanchao; Huang, Zifeng; Yang, Dongfan; Chu, Tong; Zheng, Dayuan; Ma, Wenzhe (Frontiers in Pharmacology, 2025)
BackgroundBreast cancer’s high recurrence and treatment side effects demand safer, more effective therapies. Mutations in the critical TP53 gene, which normally prevents cancer, can instead promote it. This study explores if low-dose statins can curb mutant p53 activation in breast cancer’s immune signaling, hindering tumor immune evasion.MethodsThe study used diverse breast cancer cell lines with varying p53 statuses. Techniques included Western blot, transfection, qRT-PCR, co-immunoprecipitation, nuclear fractionation, and immunohistochemistry. In vivo experiments used BALB/c mice, with bioinformatics analysis via cBioPortal.ResultsThe study found that suppressing mutant p53 restores innate immunity and enhances cancer treatment. Low-dose statins promoted IRF3 nuclear translocation by inhibiting mutant p53. Lovastatin treatment in vivo increased phosphorylated TBK1 and IRF3 levels and induced CD8+ T lymphocyte infiltration in tumors.ConclusionThe findings suggest low-dose statins can enhance innate immunity in breast cancer by degrading mutant p53, offering new treatment possibilities. Caution is advised, and further research is needed to address limitations and provide solid evidence for clinical use.